2020
DOI: 10.1371/journal.pone.0229300
|View full text |Cite
|
Sign up to set email alerts
|

Lung clearance index in healthy volunteers, measured using a novel portable system with a closed circuit wash-in

Abstract: Introduction Lung clearance index (LCI) is a sensitive measure of early lung disease, but adoption into clinical practice has been slow. Challenges include the time taken to perform each test. We recently described a closed-circuit inert gas wash-in method that reduces overall testing time by decreasing the time to equilibration. The aim of this study was to define a normative range of LCI in healthy adults and children derived using this method. We were also interested in the feasibility of using this system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The MBW test is repeatable, reproducible, and user-friendly [42]. The narrow (essentially fixed) range of LCI values across different populations and ages [33,34,39,56,57] makes it a useful marker for tracking disease progression [14]. Abnormal LCI values can be detected in patients with CF shortly after birth [53], which corroborates the separate observations of early lung inflammation in the absence of infection [54].…”
Section: Multiple-breath Washout Test (Lung Clearance Index)supporting
confidence: 58%
“…The MBW test is repeatable, reproducible, and user-friendly [42]. The narrow (essentially fixed) range of LCI values across different populations and ages [33,34,39,56,57] makes it a useful marker for tracking disease progression [14]. Abnormal LCI values can be detected in patients with CF shortly after birth [53], which corroborates the separate observations of early lung inflammation in the absence of infection [54].…”
Section: Multiple-breath Washout Test (Lung Clearance Index)supporting
confidence: 58%
“…No correlation between age and LCI was found when including younger collectives. 27 28 With the normal range appearing to remain stable for the first four decades of life, a fixed ULN of 6.8 and 7.0 was proposed by Horsley et al 28 and Fuchs et al 29 In patients older than 40 years a larger dispersion was seen. Despite all of these approaches being based on SF 6 , small differences may be partly explained by system set-ups and tracer gas concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Agreeing on an upper limit of normal for LCI was challenging. Based on a study conducted in different hospitals in the United Kingdom, LCI was found to have a wider range of normal results for adults than for children [7]. In addition, multiple MBW devices exist at present, and the values of LCI are not interchangeable.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry is, in fact, limited in its ability because it is dependent on the airway resistance, which is very low in the airways starting at the eighth to tenth generation. MBW has been proven to be useful in patients with CF, but its place in the follow-up of patients with PCD-BE and nCFnPCD-BE remains unclear [7]. Studies conducted on MBW in PCD-BE patients are conflicting and often not comparable because of differences in MBW devices, tracer gases, and the equipment being used [8].…”
Section: Introductionmentioning
confidence: 99%